Request of the Spanish Government for the technical assistance of the League in the study of measures for providing food supplies for refugees (report) - Bray, Denys, 1875-1951
1938-11-03 032-0199-008 - 7 - ANNEX I Letter, dated September 20th, 1938, from the Spanish Minister for Foreign Affairs to the Secretary-General. "As you are aware, the Spanish Government is faced with the grave and urgent problem of ensuring the supply of food during the coming winter for approximately three million refugees who have come from the territory in the hands of the rebel authorities to the territory that has remained under the authority of the Government of the Republic. "Although this is clearly a humanitarian problem, its solution obviously presents important economic and financial aspects. For that reason, I have the honour to approach you on my Government's behalf and to request you to arrange for the competent organisations of the League of Nations to afford their invaluable help to the competent Spanish services in the study of the question, with a view to finding the best possible solution. I venture to emphasise the urgency of the question, more especially in view of the near approach of winter "I am able to inform you that the Spanish Government would see no objection, if the same need were felt in the part of the territory which is in the hands of the rebel authorities, to the extension of the League's beneficent action to the whole of the national territory of Spain. "The Spanish delegation is at the disposal of the League's organs for the purpose of considering any point arising out of the present request. (signed) ALVAREZ DEL VAYO " 292/946/32/199(vii)